Efficacy and safety results of micellar water, cream and serum for rosacea in comparison to a control group. (21st July 2020) - Guertler, Anne; Jøntvedt, Nora Marie; Clanner‐Engelshofen, Benjamin M.; Cappello, Christian; Sager, Angelika; Reinholz, Markus
Abstract: Background: Rosacea is a common inflammatory skin disorder with centrofacial erythema, flushing, telangiectasia, papules/pustules, and possible ocular or phymatous manifestation. Patients' skin is particularly sensitive to chemical and physical stimuli leading to burning, stinging, dryness, and skin tightness. Objective: Dermatological evaluation of the efficacy and safety of skin care products designed for centrofacial erythema in rosacea patients, in comparison with a control group using objective measurements. Rosacea symptoms (itching, tension, warmth, burning, dryness) and quality of life were examined. Methods: Sixty Caucasians with centrofacial erythema were enrolled in an 8‐week prospective study, fifty of them exclusively using the study products (micellar water, cream, and serum) with ten participants randomly assigned to a control group. Patients were evaluated at baseline (V0), at 4 weeks (V1), and at 8 weeks (V2). Three‐dimensional objective measurements (VECTRA ® ) as well as standardized questionnaires were used. Results: Results were compared with the control group. A significant reduction of 16% in skin redness as indicated by VECTRA ® analysis was seen in the intervention group comparing V0‐V2. Furthermore, rosacea‐associated symptoms diminished by 57.1%, while life quality of affected patients within the intervention group improved by 54.5% comparing V0‐V2, respectively. Conclusions: A skin care regime suitable for sensitive and redness‐prone skin led to an enhanced clinical appearance, to a decrease of associated symptoms in rosacea patients, and to an improved life quality.